Iron-catalyzed [3 + 2]-cycloaddition of in situ generated N-ylides with alkynes or olefins: access to multi-substituted/polycyclic pyrrole derivatives. Issue 3 (2nd January 2020) - Zhou, Kai; Bao, Ming; Huang, Jingjing; Kang, Zhenghui; Xu, Xinfang; Hu, Wenhao; Qian, Yu
Abstract : An iron-catalyzed three-component reaction of benzimidazoles with diazoacetates and electron-deficient alkynes or alkenes that delivers multi-substituted pyrroles, pyrrolo[1, 2- a ]benzimidazoles and pyrrolo[1, 2- a ] quinoxalinones has been reported. Abstract : An iron-catalyzed one-pot three-component reaction of 1-substituted benzimidazoles with diazoacetates and electron-deficient alkynes or alkenes has been reported. Mechanistically, the reaction goes through a 1, 3-dipolar cycloaddition of catalytically generated benzimidazolium N -ylides with various activated alkynes or alkenes, leading to multi-substituted and polycyclic fused pyrrole derivatives, respectively.